Functional and radiological outcomes between cemented and uncemented partial hip replacement in the elderly - Darak, Ajinkya Pravin; Mahajan, Amit; Hedgire , Snehal (International Journal of Research in Orthopaedics, 2026)
Background: Hemiarthroplasty (HA) is the treatment of choice for displaced intracapsular femoral neck fractures (FNFs) in elderly patients. However, the optimal method of fixation-cemented or uncemented-remains controversial, particularly in the Indian population. This study aimed to compare the functional and radiological outcomes of cemented versus uncemented HA (UCHA) in elderly patients. Methods: A retro-prospective comparative study was conducted at a tertiary care centre from January 2021 to September 2024. Sixty-seven patients aged above 60 years with intracapsular FNFs treated with HA were included. Patients were divided into cemented (n=44) and uncemented (n=23) groups. Functional outcome was assessed using the Harris hip score (HHS), and radiological evaluation focused on prosthetic subsidence at 6 months postoperatively. Statistical analysis was performed using SPSS version 29.0 with p<0.05 considered significant. Results: The mean age of patients was 72.37±8.1 years, with females comprising 55% of the cohort. At 6 months, no statistically significant difference was observed in HHS between the cemented and uncemented groups (p=0.132). Good functional outcomes were seen in 52.6% of the cemented group and 54.5% of the uncemented group. Prosthetic subsidence was higher in the uncemented group (13.04%) compared to the cemented group (2.63%), though the difference was not statistically significant (p=0.135). No major complications were reported. Conclusions: Cemented and UCHA showed comparable short-term functional outcomes. However, uncemented fixation demonstrated a higher trend toward prosthetic subsidence. Larger studies with longer follow-up recommended.